Crack Formation on Crystalline Bismuth Oxychloride Thin Square Sheets by Using a Wet‐Chemical Method. Issue 5 (25th March 2020) - Yi, Ronghua; Wang, Yaoli; Zhou, Xu; Li, Zhuoyao; Zhang, Chengyu; He, Chengyu; Li, Hai; Gao, Yongqian; Huang, Xiao; Lu, Gang
Abstract: The morphology of nanocrystals is crucial in modulating their properties including optical, chemical and catalytic ones. For the intensively studied sheet‐like structures, it is also important to engineer their detailed nanostructures on sheet surfaces. In this work, micron‐sized bismuth oxychloride (BiOCl) thin square sheets in tetragonal matlockite‐like phase and the corner‐truncated ones were successfully synthesized by using a simple wet‐chemical method. These square sheets could be partially etched, forming surface cracks with the size and density easily tuned. Two different types of cracks were observed on the surfaces of the corner un‐truncated and truncated BiOCl square sheets. Surprisingly, radial cracks formed on the corner‐truncated BiOCl sheets, which is attributed to the existence of physical stress during the etching and is highly related to the original nanostructure of the BiOCl sheets. This work provides a wet‐chemical method for engineering surface cracks, especially radial cracks, on the surfaces of BiOCl nanosheets, which may be expanded to surface engineering of other nanosheets and will show a great potential in various fields. Abstract : Being on the square : Single‐crystalline BiOCl thin square sheets and corner‐truncated ones were successfully synthesized with a wet‐chemical method. The thin sheets could be partially etched, forming surface cracks. Moreover, radial cracks were surprisingly observed on the corner‐truncated BiOCl sheets.